De La Garza Toledo, Enrique (compilador), Sindicatos y nuevos movimientos sociales en América Latina, 1ª ed., CLACSO, Buenos Aires, 2005 - Martinelli, Larisa (2006)
Fil: Fil: Martinelli, Larisa; Universidad Nacional de Rosario. Argentina